2019
DOI: 10.1055/a-0867-9599
|View full text |Cite
|
Sign up to set email alerts
|

Practical applications and learning curve for EUS-guided hepaticoenterostomy: results of a large single-center US retrospective analysis

Abstract: Background and study aims Endoscopic ultrasound-guided hepaticoenterostomy (EUS-HE) is an effective method of endoscopic biliary drainage in cases where endoscopic retrograde cholangiopancreatography has failed or is deemed impossible. Indications for EUS-HE have expanded, resulting in increased interest by endoscopists to learn the procedure; however, few data exist on breadth of application or experience needed to develop proficiency. We describe utilization of EUS-HE for biliary decompression at a large ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
1
9
1
Order By: Relevance
“…This study was undertaken a decade after the adoption of EUS-DAD at our center. Operators were well past the learning curve of EUS-DAD, estimated at 30 -40 cases [31,32]. EUS-DAD was ingrained into our institutional treatment algorithms and referral pathways at the time of this evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was undertaken a decade after the adoption of EUS-DAD at our center. Operators were well past the learning curve of EUS-DAD, estimated at 30 -40 cases [31,32]. EUS-DAD was ingrained into our institutional treatment algorithms and referral pathways at the time of this evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…This study was undertaken a decade after the adoption of EUS-DAD at our center. Operators were well past the learning curve of EUS-DAD, estimated at 30-40 cases[31,32]. EUS-DAD was ingrained into our institutional treatment algorithms and referral pathways at the time of evaluation.Our study is unique in that it includes all potential candidate patients, both intervention naïve and those with prior interventions, both biliary and pancreatic target ducts, and both benign and malignant indications.…”
mentioning
confidence: 99%
“…There definitely is a steep learning curve, requiring about 40 cases to achieve competence. Interestingly, after the initial 40 cases, the success rate appears to be close to 100 % [9]. When EUS-BD becomes ingrained into ERCP practice, PTBD will effectively be relegated to a third-line ductal drainage option.…”
mentioning
confidence: 99%
“…Even in the hands of experienced interventional endoscopists, there is undoubtedly a learning curve for advanced EUS procedures. For EUS-guided biliary drainage, around 30 to 40 cases are needed to achieve proficiency and more to achieve true mastery of the technique [20,21]. We have recently looked at the learning curve for EUS-GE using cumulative sum analysis and have found that around 25 cases are needed to achieve proficiency and 40 cases to achieve mastery [22].…”
mentioning
confidence: 99%